2020
DOI: 10.31703/grr.2020(v-ii).12
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Shyness and Lack of Confidence as Psychological Barriers on EFL Learners' Speaking Skills: A Case Study of South Punjab

Abstract: This work investigated the effects of shyness and lack of confidence as psychological barriers on EFL learner' speaking skill, particularly at the public sector colleges, universities and the sub-campuses of these universities located in the South Punjab, Pakistan. This project was scheduled to use a mixed-method type. Majority of the students indicated that there is an insignificant and negative relationship between the variables of shyness, lack of confidence and speaking English achievements. Since, as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Additionally, this study showed that many STEM learners mentioned being anxious and shy to speak English. Supporting the findings, a study that looked into the factors affecting English language learners' shyness reported that they had limited knowledge of the language, resulting in anxiety (Ahsan et al, 2020 ). This is an issue among second or foreign language learners, where they need to acquire vocabulary to use the English language proficiently.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Additionally, this study showed that many STEM learners mentioned being anxious and shy to speak English. Supporting the findings, a study that looked into the factors affecting English language learners' shyness reported that they had limited knowledge of the language, resulting in anxiety (Ahsan et al, 2020 ). This is an issue among second or foreign language learners, where they need to acquire vocabulary to use the English language proficiently.…”
Section: Discussionmentioning
confidence: 80%
“…A study reported that one of the factors associated with the difficulties in learning the second language is the lack of vocabulary (Misbah et al, 2017 ). Similarly, studies reported that one barrier to learning English includes anxiety (Ahsan et al, 2020 ) due to teachers' inability to scaffold language learning (Nasr et al, 2020 ). In traditional classroom teaching and learning, Vygotsky mentioned the vital role to scaffold learning (Vygotsky, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…They further concluded that the relationship was more significant among female learners. Similarly, Ahsan et al (2020) observed the role of shyness in EFL learners’ speaking skill among 200 college and university students in South Punjab. They employed a structured researcher-made questionnaire to determine the degree of shyness.…”
Section: Empirical Studiesmentioning
confidence: 86%
“…In a similar vein, Baldwin and Caroline (2011) asserted that engaging in verbal interactions is more likely to develop anxiety and shyness among language learners. Therefore, it will be essential to promote learners’ communicative competence and encourage them to implement their English knowledge despite the probable mistakes and difficulties ( Ahsan et al, 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation